Pyrimidin‐6‐yl Trifluoroborate Salts as Versatile Templates for Heterocycle Synthesis. Issue 17 (17th March 2021) - Cousins, David L.; Fricero, Prisca; Kopf, Kenji P. M.; McColl, Elliot J.; Czechtizky, Werngard; Lim, Yee Hwee; Harrity, Joseph P. A.
Abstract: We report a novel and general method to access a highly under‐studied privileged scaffold—pyrimidines bearing a trifluoroborate at C4, and highlight the broad utility of these intermediates in a rich array of downstream functionalization reactions. This chemistry is underpinned by the unique features of the trifluoroborate group; its robustness provides an opportunity to carry out chemoselective reactions at other positions on the pyrimidine while providing a pathway for elaboration at the C−B bond when suitably activated. Abstract : Stable and enabling: Pyrimidine trifluoroborates are an under‐developed scaffold that have been rarely reported in the literature. These compounds participate in a rich array of downstream functionalization reactions that are underpinned by the unique features of the trifluoroborate group; its robustness provides an opportunity to carry out chemoselective reactions at other positions on the pyrimidine while providing a pathway for elaboration at the C−B bond when activated.